Lattice Orientation Heredity in the Transformation of 2D Epitaxial Films. Issue 4 (6th December 2021) - Xu, Xiangming; Smajic, Jasmin; Li, Kuang‐hui; Min, Jung‐Wook; Lei, Yongjiu; Davaasuren, Bambar; He, Xin; Zhang, Xixiang; Ooi, Boon S.; Costa, Pedro M. F. J.; Alshareef, Husam N.
Abstract: The ability to control lattice orientation is often an essential requirement in the growth of both 2D van der Waals (vdW) layered and nonlayered thin films. Here, a unique and universal phenomenon termed "lattice orientation heredity" (LOH) is reported. LOH enables product films (including 2D‐layered materials) to inherit the lattice orientation from reactant films in a chemical conversion process, excluding the requirement on the substrate lattice order. The process universality is demonstrated by investigating the lattice transformations in the carbonization, nitridation, and sulfurization of epitaxial MoO2, ZnO, and In2 O3 thin films. Their resultant compounds all inherit the mono‐oriented crystal feature from their precursor oxides, including 2D vdW‐layered semiconductors (e.g., MoS2 ), metallic films (e.g., MXene‐like Mo2 C and MoN), wide‐bandgap semiconductors (e.g., hexagonal ZnS), and ferroelectric semiconductors (e.g., In2 S3 ). Using LOH‐grown MoN as a seeding layer, mono‐oriented GaN is achieved on an amorphous quartz substrate. The LOH process presents a universal strategy capable of growing epitaxial thin films (including 2D vdW‐layered materials) not only on single‐crystalline but also on noncrystalline substrates. Abstract : Lattice orientation heredity is shown to be a universal strategy in the transformation of highly oriented 2D van der Waals layered and nonlayered thin films. Different from the classical and direct epitaxial deposition, this process is developed based on the heredity phenomena in material science. It opens a new window for growing textured films on disordered substrates (e.g., GaN‐related technology), and provides an effective route for large‐area growth of epitaxial 2D MoS2 thin films.